An Effort to Increase Students' Learning Motivation Using Ice-Breaking Techniques in Class II: A Service in SD Negeri 09 Indralaya - Rodiatun Niswah; Dian Andesta Bujuri; Ahmad Lamsari; Murlita; Febri Pramudya Wardani; Andi (PT Pustaka Cendekia Publisher, 2025)
This study aims to determine the increase in student learning motivation using ice-breaking techniques in grade II of SD Negeri 09 Indralaya. The research method used is qualitative descriptive with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study are the second-grade students of SD Negeri 09 Indralaya for the 2023/2024 school year, totaling 36 students. With the implementation of ice-breaking, it is to eliminate boredom, boredom, and tension in the learning process. Based on the results of the study show that the application of ice-breaking can increase student learning motivation. So that students can easily absorb the material given by the teacher.